Síntese e avaliação das atividades leishmanicida e tripanocida de derivados 1,3-Bisariloxi-2-Aminopropano - Stefania Neiva Lavorato (2016)
We describe herein the synthesis and evaluation of the antileishmanial and antitrypanosomal activity of novel 1,3-bis(aryloxy)propan-2-amines, designed by aryloxyl variation of hit compounds 1,3-bis(3-nitrophenoxy)propan-2-amine (1) and 1,3-bis(1-naphthyloxy)propan-2-amine (2), discovered during an in-house chemical library screening. Bisaryloxypropanamines were prepared in four steps, starting from epichlorohydrin and the appropriate phenol, in global yields that ranged from 9 to 58%. Three novel amines - 4-methylphenyl, 3-chlorophenyl and 4-chlorophenyl presented a higher antileishmanial activity against L. amazonensis promastigotes than hit 1 (IC50 = 10.6 µM). 2-Methylphenyl and 4-methylphenyl amines showed the best profiles in the treatment of L. amazonensis-infected murine macrophages. Regarding the antitrypanosomal activity, four amines, 3-cyanophenyl, 4-nitrophenyl, 2-methylphenyl and 2-chlorophenyl, were more active than hit 2 (IC50 = 12.5 µM) against T. cruzi-infected L929 fibroblasts. The aromatic substituent effects and their physicochemical contributions were determined by structure-activity relationship analysis. We also evaluated the biological potential of 1,3-bis(aryloxy)propan-2-ols, intermediates to obtain 1,3-bis(aryloxy)propan-2-amines. Moreover, the synthesis of 21 N-substituted amines was carried out by reductive amination or nucleophilic substitution, which provided higher yields regarding to the former. In general, the replacement of amino group by hydroxyl group as well as the introduction of a substituent into the amino group did not contribute to activity enhancement, demonstrating the importance of primary amine to activity. Most compounds presented moderate or low selectivity of action, showing that, despite the relevant antileishmanial and antitrypanosomal activity of those compounds, further studies are required in order to optimize their antiparasitic activity, ensuring selectivity of action.